The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.1002/mgg3.368
|View full text |Cite
|
Sign up to set email alerts
|

A genetic variant in IL‐15Rα correlates with physical activity among European–American adults

Abstract: BackgroundInterleukin‐15 (IL‐15) is a myokine associated with muscle strength, possibly by attenuating protein breakdown. A variant in the alpha‐receptor (IL‐15Rα 1775 A>C, rs2228059) partially modulates the muscle strength and size response to resistance training. We examined if this polymorphism associated with habitual physical activity among European‐American adults.MethodsMen (n = 240, 23.7 ± 0.3 year, body mass index [BMI] 25.3 ± 0.3 kg/m2) and women (n = 292, 23.2 ± 0.3 year, 24.0 ± 0.3 kg/m2) were geno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 49 publications
0
5
0
Order By: Relevance
“…Among the 48 candidate gene studies, the scores varied from 1 to 9.5, with a median of 6.5. Three candidate gene studies were considered high quality [ 32 , 33 , 41 ], 35 medium quality, while 10 studies were considered low or very low quality.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Among the 48 candidate gene studies, the scores varied from 1 to 9.5, with a median of 6.5. Three candidate gene studies were considered high quality [ 32 , 33 , 41 ], 35 medium quality, while 10 studies were considered low or very low quality.…”
Section: Resultsmentioning
confidence: 99%
“…However, the GWAS by Lin et al [ 31 ] and De Moor et al [ 28 ] did not successfully replicate SNPs in or close to the ACE gene. In another high quality candidate gene study, Bruneau et al [ 33 ] found an association between light intensity physical activity and a SNP in IL15RA (rs2228059). In total, variants in nine candidate genes ( ACE, CASR, CYP19A, FTO, DRD2, CNR1, LEPR, MC4R, NPC1 ) were found to be associated with physical activity or sedentary behaviour in more than one study.…”
Section: Resultsmentioning
confidence: 99%
“…The PubMed search yielded 902 results, of which 12 studies met the three-inclusion criterion. Two papers [21,22] were added due to appearance in the literature after the initial search. Of the 14 studies, seven were GWAS and seven were candidate gene studies.…”
Section: Resultsmentioning
confidence: 99%
“…The pre-2009 studies that used micro-satellite technology did not provide specific locations for conservation or age predictions and as a result, were dropped from the analysis. After compiling all results, the eight included studies included reported a total of 104 unique SNPs significantly associated with PA [2129].…”
Section: Resultsmentioning
confidence: 99%
“…Following Mackinnon's mediation approach, the direct, indirect, and total effects were estimated using bias‐corrected bootstrap CI (bootstrap = 5000); indirect effects were considered significant if the 95% CI do not contain 0 (Zhao et al., 2010). Weekly physical activity was log‐transformed to reduce the skewness and normalize the distribution based on previous recommendation (Beyler, 2010; Bruneau et al., 2018). Again, probit model with WLSMV was used due to the binary outcome of metabolic syndrome.…”
Section: Methodsmentioning
confidence: 99%